Two coregulated efflux transporters modulate intracellular heme and protoporphyrin IX availability in Streptococcus agalactiae. - Annabelle Fernandez (Public Library of Science (PLoS), 2010)
Streptococcus agalactiae is a major neonatal pathogen whose infectious route involves septicemia. This pathogen does not synthesize heme, but scavenges it from blood to activate a respiration metabolism, which increases bacterial cell density and is required for full virulence. Factors that regulate heme pools in S. agalactiae are unknown. Here we report that one main strategy of heme and protoporphyrin IX (PPIX) homeostasis in S. agalactiae is based on a regulated system of efflux using two newly characterized operons, gbs1753 gbs1752 (called pefA pefB), and gbs1402 gbs1401 gbs1400 (called pefR pefC pefD), where pef stands for 'porphyrin-regulated efflux'. In vitro and in vivo data show that PefR, a MarR-superfamily protein, is a repressor of both operons. Heme or PPIX both alleviate PefR-mediated repression. We show that bacteria inactivated for both Pef efflux systems display accrued sensitivity to these porphyrins, and give evidence that they accumulate intracellularly. The DeltapefR mutant, in which both pef operons are up-regulated, is defective for heme-dependent respiration, and attenuated for virulence. We conclude that this new efflux regulon controls intracellular heme and PPIX availability in S. agalactiae, and is needed for its capacity to undergo respiration metabolism, and to infect the host.